PENGARUH KAPITALISASI PASAR, PERTUMBUHAN PENJUALAN, RISIKO BISNIS TERHADAP RETURN SAHAM - Bahantwelu, Maria Immaculata; Tkela, Melianus E.; Klau, Herlina Helmy; Astuti, Novising Dewi (Universitas Nusa Cendana, 2025)
Stock return is the ratio of returns, which can be in the form of profit or loss, received by investors as a result of their investment in a particular company. The purpose of this study is to determine the impact of market capitalization, sales growth, and business risk on stock returns in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The method used in this study is quantitative. The population in this study consisted of 50 companies, while a sample of 17 companies was taken using a purposive sampling technique. Data regarding financial statements were taken from www.idx.co.id and analyzed using SPSS version 22. From the results of the study, it can be concluded that: 1) market capitalization has a significant influence on stock returns, 2) sales growth also has a significant impact on stock returns, 3) business risk has a significant effect on stock returns, and 4) market capitalization, sales growth, and business risk simultaneously influence stock returns.